Immunization with CSP and a RIG-I Agonist is Effective in Inducing a Functional and Protective Humoral Response Against Plasmodium - Teixeira, Ana Rafaela; Pérez-Cabezas, Begoña; Costa, David M.; Sá, Mónica; Golba, Sylvain; Sefiane-Djemaoune, Hélèna; Ribeiro, Joana; Kaneko, Izumi; Iwanaga, Shiroh; Yuda, Masao; Tsuji, Moriya; Boscardin, Silvia Beatriz; et al. (Frontiers in Immunology, 2022)
Malaria is a major public health concern, as a highly effective human vaccine remains elusive. The efficacy of a subunit vaccine targeting the most abundant protein of the sporozoite surface, the circumsporozoite protein (CSP) has been hindered by difficulties in generating an effective humoral response in both quantity and quality. Using the rodent Plasmodium yoelii model we report here that immunization with CSP adjuvanted with 5’ppp-dsRNA, a RIG-I agonist, confers early and long-lasting sterile protection in mice against stringent sporozoite and mosquito bite challenges. The immunization induced high levels of antibodies, which were functional in targeting and killing the sporozoites and were sustained over time through the accumulation of long-lived plasma cells in the bone marrow. Moreover, 5’ppp-dsRNA-adjuvanted immunization with the CSP of P. falciparum was also significantly protective against challenges using a transgenic PfCSP-expressing P. yoelii parasite. Conversely, using the TLR3 agonist poly(A:U) as adjuvant resulted in a formulation that despite inducing high antibody levels was unable to generate equally functional antibodies and was, consequently, less protective. In conclusion, we demonstrate that using 5’ppp-dsRNA as an adjuvant to vaccines targeting CSP induces effective anti-Plasmodium humoral immunity.